The Schizosaccharomyces pombe spindle checkpoint protein mad2p blocks anaphase and genetically interacts with the anaphase-promoting complex - He, Xiangwei (The National Academy of Sciences of the USA, 1997)
The spindle checkpoint monitors mitotic spindle integrity and the attachment of kinetochores to the spindle. Upon sensing a defect the checkpoint blocks cell cycle progression and thereby prevents chromosome missegregation. Previous studies in budding yeast show that the activated spindle checkpoint inhibits the onset of anaphase by an unknown mechanism. One possible target of the spindle checkpoint is anaphase promoting complex (APC), which controls all postmetaphase events that are blocked by spindle checkpoint activation. We have isolated mad2, a spindle checkpoint component in fission yeast, and shown that mad2 overexpression activates the checkpoint and causes a cell cycle arrest at the metaphase-to-anaphase transition. In addition to the observation that mad2-induced arrest can be partially relieved by mitosis-promoting factor inactivation, we present genetic evidence consistent with the hypothesis that the spindle checkpoint imposes a cell cycle arrest by inhibiting APC-dependent proteolysis.